2021
DOI: 10.3390/metabo11120873
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of In Vitro Hair Cell-like Cell Differentiation from Human Embryonic Stem Cells through the Regulation of Notch Signaling

Abstract: The Notch signaling pathway plays an important role in otic neurogenesis by regulating the differentiation of inner ear hair cells and supporting cells. Notch-regulated differentiation is required for the regeneration of hair cells in the inner ear. The temporal expression pattern of Notch ligands and receptors during in vitro hair cell-like cell differentiation from human embryonic stem cells (hESCs) was detected by quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Subsequently, pAJ-U6-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Therefore, we speculated that the phenotype of HC loss emerging in the ndrg2 mutants was due to the defects of HC differentiation. Notch-mediated lateral inhibition is widely believed to regulate HC versus supporting cell specification while suppression of Notch signaling promotes the differentiation of HCs from the supporting cells [ 4 , 6 , 32 , 33 , 34 , 35 ]. To verify whether the ndrg2 gene affected HC differentiation through the Notch signaling pathway, a Notch γ-secretase inhibitor LY411575 was used to treat the ndrg2 mutants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we speculated that the phenotype of HC loss emerging in the ndrg2 mutants was due to the defects of HC differentiation. Notch-mediated lateral inhibition is widely believed to regulate HC versus supporting cell specification while suppression of Notch signaling promotes the differentiation of HCs from the supporting cells [ 4 , 6 , 32 , 33 , 34 , 35 ]. To verify whether the ndrg2 gene affected HC differentiation through the Notch signaling pathway, a Notch γ-secretase inhibitor LY411575 was used to treat the ndrg2 mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Development of HCs is an extremely complex and highly coordinated process and it is regulated by a series of key factors involving multiple signaling pathways, such as Notch/Wnt/Atoh1, MAPK, PI3K/Akt, calcium channels and oxidative stress/ROS [ 4 , 5 , 6 , 7 , 8 ]. The classical and conserved Notch signaling pathway plays critical roles in the development and regeneration of HCs [ 3 , 4 , 5 , 6 , 32 ]. Studies suggested that Notch-mediated lateral inhibition determined the cell fate of the sensory epithelium and modulated the HCs versus supporting cell specification by activation of Notch signaling to inhibit the neighboring HCs from differentiating into the same cell type, and then to adopt the alternative fate, that is, supporting cells [ 4 , 6 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal expression patterns of Notch signals, a key signal in regulating hair cell differentiation, were detected and the possible coreregulated roles of Notch ligand JAG2 (jagged canonical Notch ligand 2) and DLL1 (delta-like canonical Notch ligand 1) were hypothesized to be anticipated in the differentiation of hair cells. 20 In another research, F I G U R E 3 Origins of inner ear organoids. Inner ear organoids can be induced from either pluripotent or mono-potent stem cells, including inner ear stem cells, ESCs, and iPSCs.…”
Section: Multifunctional Stem Cellsmentioning
confidence: 99%
“…obtained differentiated inner ear progenitor cells cultured with N2, B27, FGF3 and FGF10 for 12 days using human ESCs cell line X1. The temporal expression patterns of Notch signals, a key signal in regulating hair cell differentiation, were detected and the possible co‐reregulated roles of Notch ligand JAG2 (jagged canonical Notch ligand 2) and DLL1 (delta‐like canonical Notch ligand 1) were hypothesized to be anticipated in the differentiation of hair cells 20 . In another research, human ESCs (WA25 cell line) were incubated in an E8 medium containing low concentrations of Matrigel and FGF to induce the differentiation of the ectoderm to form dense spherical cell clusters.…”
Section: Construction Of Inner Ear Organoidsmentioning
confidence: 99%